2017
DOI: 10.3390/beverages3040054
|View full text |Cite
|
Sign up to set email alerts
|

Raw and Heat-Treated Milk: From Public Health Risks to Nutritional Quality

Abstract: Abstract:Consumers have recently shown a preference for natural food products and ingredients and within that framework, their interest in consuming raw drinking milk has been highlighted, claiming nutritional, organoleptic and health benefits. However, a public debate has simultaneously emerged about the actual risks and benefits of direct human consumption of raw milk. This paper compares the microbiological, nutritional and sensory profile of raw and heat-treated milk, to evaluate the real risks and benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 112 publications
1
40
0
Order By: Relevance
“…The authors found that poor farm biosecurity and poor nutrition leading to ill health of the cattle were contributing management risk factors (Rahman et al, ). Consumption of raw milk by people is more likely to progress to extra‐pulmonary TB lesions (Melini, Melini, Luziatelli, & Ruzzi, ). Pasteurization completely removes M. bovis from dairy, having been designed to specifically destroy M. tuberculosis and C. burnetti (Melini et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that poor farm biosecurity and poor nutrition leading to ill health of the cattle were contributing management risk factors (Rahman et al, ). Consumption of raw milk by people is more likely to progress to extra‐pulmonary TB lesions (Melini, Melini, Luziatelli, & Ruzzi, ). Pasteurization completely removes M. bovis from dairy, having been designed to specifically destroy M. tuberculosis and C. burnetti (Melini et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of raw milk by people is more likely to progress to extra‐pulmonary TB lesions (Melini, Melini, Luziatelli, & Ruzzi, ). Pasteurization completely removes M. bovis from dairy, having been designed to specifically destroy M. tuberculosis and C. burnetti (Melini et al, ). Increased uptake of dairy pasteurization in LMICs will remove a significant risk factor for zTB infection as well as several other pathogens such as Brucella, Campylobacter, E. coli, Listeria, Staphylococcus, Streptococcus and Yersinia (Melini et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these moulds in dairy products as Aspergillus, Fusarium, Stachybotrys and Penicillium potential mycotoxin producers represents a danger for human and animal health (Abo El-Makarem et al, 2019;Alnaemi, 2019). Toxins produced by theses moulds must be taken into account when monitoring the sanitary quality of fermented dairy products intended for consumption (Melini et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Raw milk may be the source of the following food pathogens from the Enterobacteriaceae family: Salmonella spp., Shiga toxin-producing Escherichia coli [13,14]. That is why bacteria from the Enterobacteriaceae family are the indicative microorganisms for raw materials and food products, and are, accordingly, used to control the level of hygienic and sanitary practices in the process of food production [15,16].…”
Section: в даний час встановлено що штучні нейронні мережі (шнм) забmentioning
confidence: 99%